AIDING AND ABETTING SUICIDE: THE ISSUES OF STATUTORY REGULATION AND LEGAL ENFORCEMENT - VELIEV A. (Legal Bulletin)
The article deals with topical issues of qualifying crimes covered by Article 110.1 of the Criminal Code of the Russian Federation. The relevance of this work is due to both the comparative novelty of the discussed provisions and the presence of challenges related to their ambiguous interpretation in both criminal law doctrine and law enforcement practice. In this regard, the primary objective of the study is to find ways to address the shortcomings in the criminalization of such acts. General scientific and specific legal methods were applied in this study. Besides, judicial practice, legal interpretations by the Plenum of the Supreme Court of the Russian Federation, normative acts, and papers of other researchers were used. The article discusses legitimacy of joint qualification of aiding and abetting suicide, possibility of unaddressed incitement to suicide, the interrelation between offenses provided in Articles 110 and 110.1 of the Russian Criminal Code, as well as validity of sanctions for aggravated forms of aiding and abetting suicide. As a result of the research, new approaches have been proposed to address the issues discussed. Amendments to the current legislation have also been suggested.